Development of fluorescent azapentalenes to study the reactivity of hypochlorous acid and chloramines in micellar systems - Pavan, Nathália Mariana [UNESP]; Martins, Lucas Michelão [UNESP]; Augusto, Laís Cristina [UNESP]; da Silva-Filho, Luiz Carlos [UNESP]; Ximenes, Valdecir Farias [UNESP] (Elsevier, 2022)
Hypochlorous acid (HClO) is an endogenous reactive oxygen species generated by the oxidation of chloride catalyzed by myeloperoxidase (MPO). This enzyme is abundant in polymorphonuclear cells and involved in the human innate immune function. This work presents the development of a fluorescent azapentalene (C1) able to be incorporated in micelles and susceptive to HClO due to its sulfide moiety. C1 is non-fluorescent in the aqueous medium but fluoresces when incorporated in micelles produced by surfactants such as sodium dodecyl sulfate (SDS), Triton X-100, and cetyltrimethylammonium chloride (CTAC). The addition of HClO promoted instantaneous fluorescence decay of C1 incorporated in SDS but not in Triton X-100 or CTAC, showing the higher accessibility of HClO to the SDS micelle core. The reactivity of C1 was also studied in the presence of amine compounds taurine, 4-aminobutanoic acid (GABA), and its ethyl ester (GABA-EE), leading to the formation of the respective chloramines. The reactivity increased with the GABA-EE, evidencing the higher accessibility to the micellar core due to the hydrophobic character of the ester derivative. The potentiality of the system to monitor the enzymatic production of HClO was demonstrated by using MPO and hydrogen peroxide (H2O2). Scavengers of HClO were applied to validate the method. In conclusion, applying C1 opens new possibilities for studying the biochemical properties of HClO and chloramines in micelles.
Keywords: Chloramines; Fluorescent probes; GABA; Hypochlorous acid; Micelles; Myeloperoxidase